Proto-Endocrinological Theories of Masculinity/Femininity (1490–1904). - Janssen, Diederik F. (Archives of Sexual Behavior, 2024)
From the mid-seventeenth century, resorption of a testicular "ferment" and resorption of some part of the semen constituted reputable accounts of secondary sexual characteristics. Only in the early twentieth century was the latter, "recrementitious secretion" theory, explicitly considered superseded by one of internal secretion, an advance ushering in the hormone era. A reconstruction of these proto-endocrinological concepts is offered onward from the first, 1490 print edition of Galen's On Semen. Early modern physicians picking up from Galen deliberated widely on the medium and pathway of male and female testicular influences on "the entire body," including the mind, causing "femininity" and "masculinity" in physical, mental–temperamental, and behavioral terms. A switch is discernible from "heat and strength" (Galen) to blood-borne "virility" or testicular vapor (such as proposed in 1564 by Tomás Rodrigues da Veiga), to iatrochemical postulations of a "seminal ferment" (suggested in the late 1650s, perhaps independently, by Thomas Willis at Oxford and Lambert van Velthuysen in Utrecht), finally to a "seminal recrement" or "reabsorbed semen" concept soon after (emergent in the posthumous work of Giovanni Alfonso Borelli, among others). During the late eighteenth century, mounting controversy surrounded both the very idea of that concept and the involved anatomical pathways, informed by multiple experiments.